Political Communication Strategies of the NasDem Party Through the Indonesian Restoration Movement in Securing Electoral Support in the 2024 General Election in North Sumatra - Ahmad Tamrin Sikumbang; Anang Anas Azhar; M. Taufiq Hidayah Tanjung (DAWUH : Islamic Communication Journal, 2025)
This study examines the political communication strategy of the NasDem Party in North Sumatra during the 2024 General Election, focusing on how the Indonesian Restoration Movement (Gerakan Restorasi Indonesia) functioned as a central narrative in shaping voter perception, party identity, and electoral outcomes. Employing a qualitative research approach, the study collected data through in-depth interviews, field observations, and document analysis. The analytical framework is grounded in Stuart Hall’s Encoding–Decoding theory, enabling an exploration of how political messages were constructed and interpreted within the socio-cultural context of North Sumatra. The findings indicate that NasDem’s communication strategy was institutionalized and implemented through four integrated components: (1) the use of simple and contextually grounded political language, (2) consistent deployment of symbolic political identity, (3) hybrid integration of grassroots mobilization and digital media, and (4) sustained two-way communication with the public. This strategy effectively reduced the cognitive distance between political ideology and everyday life, fostered emotional proximity between the party and voters, and strengthened long-term voter loyalty. The party’s stable electoral growth from 2014 to 2024 confirms that sustainable reminder of political success is driven not by campaign intensity alone, but by the continuous institutionalization of culturally resonant, emotionally engaging, and participatory communication practices. This study contributes to political communication scholarship by extending the application of the Encoding–Decoding model to regional Indonesian politics and demonstrating the importance of long-term communication institutionalization in sustaining electoral support and democratic engagement.